Ligand design and its influence on the photophysical and structural properties of dinuclear and tetranuclear copper and silver complexes - Gipper, Jordan Robert (My University, 2025)
Fluorescent molecules are used in a vast range of applications such as in organic light-emitting diodes (OLEDs) and thermally activated delayed fluorescence (TADF) emitters; however, many promising candidates lack the ability to fluoresce in the solid state which is needed in the manufacturing of these materials. Herein, the synthesis of a novel bidentate ligand, 2-methyl-N¬-((5-(2-(thiophen-2-yl)propan-2-yl)-1H-pyrrol-2-yl)methyl)propan-2-amine or SNNHtBu, and the corresponding dinuclear copper (I) and silver (I) complexes are reported with metal-metal bond interactions of 2.686 Å for [CuSNNHtBu]₂ and 2.88 Å for [AgSNNHtBu]₂. OLEDs and thermally activated delayed fluorescent (TADF) emitters are becoming a more common feature used in display technologies. A desire to move away from heavy and rare earth metals has made Copper (I) or Cu[superscript I] a desirable alternative. However, fine tuning of the excitation and emission properties of these complexes is of high importance. As such, we report the structural modification of a previously reported thiophene containing SNN dincuclear Cu[superscript I] complex. The synthesis, characterization, and fluorescent properties of two new ligands are investigated. Coordination of these two new ligands along with NNHtBu to Cu[superscript I] are conducted. These three new dinuclear Cu[superscript I] complexes are synthesized, characterized and their fluorescent and structural properties are compared and contrasted against themselves and the parent compound of [CuSNNHtBu]₂. Copper assemblies play a vital role in biologal and synthetic processes alike. A recent advancement in extended metal chain assemblies has received significant attention due to their application in small molecule activation, in multielectron processes, and fluorescence. Schiff-base calix[2]pyrrole complexes for nickel (II) and palladium (II) have been previously reported for their use in hydrogen evolution. Herein, the utilization of symmetrical and unsymmetrical Schiff-base calix[2]pyrroles for coordination of Cu (I) to synthesize tetranuclear complexes is explored. By varying the substituents at the quaternary carbon, it was found that two different assemblies, either a distorted square-planar or a bent tetranuclear linear chain assembly were formed. Investigations also include looking into the effects of the imine on the system.
Keywords: Dinuclear copper (I); Tetranuclear copper (I); Fluorescence